2020
DOI: 10.1007/s40684-020-00277-5
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Functional Microarchitected Reactors for Energy, Environmental, and Biological Applications

Abstract: The use of microreactors in the continuous fluidic system has been rapidly expanded over the past three decades. Developments in materials science and engineering have accelerated the advancement of the microreactor technology, enabling it to play a critical role in chemical, biological, and energy applications. The emerging paradigm of digital additive manufacturing broadens the range of the material flexibility, innovative structural design, and new functionality of the conventional microreactor system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 99 publications
(184 reference statements)
0
13
0
2
Order By: Relevance
“…[186] The flow pattern and the convection domain are affected by the minimum size of channels and maximum size of the overall dimensions. [4,27] The minimum channel size is associated with printing resolutions, while the maximum overall size is determined by the building platform. As shown in Figure 9b, the structures with the maximum lengths of 1500 and 1000 mm can be printed with the SLA and FDM methods, respectively.…”
Section: Selection Of 3d Printing Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[186] The flow pattern and the convection domain are affected by the minimum size of channels and maximum size of the overall dimensions. [4,27] The minimum channel size is associated with printing resolutions, while the maximum overall size is determined by the building platform. As shown in Figure 9b, the structures with the maximum lengths of 1500 and 1000 mm can be printed with the SLA and FDM methods, respectively.…”
Section: Selection Of 3d Printing Technologiesmentioning
confidence: 99%
“…In the commercial additively manufacturing, the printers are devoted to fabricating the structures with compact matrix, since the strength and toughness are the two factors to assess the commercial AM. [2,4,8] On the contrary, the 3D printing of HSCs is quite different for its requirement on the presence of pores in the matrix of the obtained structures. For the same reason, the activity and the porosity are not emphasized in the commercial AM.…”
Section: Am For Hierarchically Structured Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, casting methods using 3D-printed molds have been widely researched owing to their advantages and applicability to various fields with different commercial materials (filaments). In addition, recent studies have revealed the capability of 3D printing to express micropatterns, and its uses on hydrophobic surfaces 27 , microchannels 28 , 29 , and moisture capture 30 . In general, the quality (surface roughness) of the end products printed by FFF-type 3D printer highly depends on various printing conditions such as printing speed, nozzle size, filament thickness, printing resolution, printing angle, and extruder temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Определенным оправданием служит крайняя малость коэффициента поглощения газа и близость его показателя преломления к единице. Однако достигаемая в прецизионных устройствах точность печати достигает величин микронного диапазона [8], что требует учета влияния наличия газа в установке (камере) на распространение излучения. Этой задаче и посвящена настоящая заметка.…”
unclassified